Comprehensive evaluation on the stability of deposit slope from reservoir bank. Issue 6 (October 2021) - Yang, Qi; Chen, Zai Qian; Zhang, Dong Dong; Shi, Ya
Abstract: In the construction of hydropower station in high mountains and canyons of southwest China, it is common to encounter deposit slopes of scattered collapse and debris flow. The deposit is formed by multi-phase and multi-genesis. Their material composition is dominated by crushed and lumpy rock and soil, and their structure is relatively dense. In natural conditions, the failure mode is mostly small-scale collapse, which has little influence on the project. With the construction of hydropower station, some deposits will be partially or completely submerged after reservoir impoundment. In reservoir impoundment condition, the stability of the deposit body decreases, and the local instability of the deposit body may cause the overall instability of the bank slope, resulting in surges and thereby endangering the safety of the dam and residents nearby. In this paper, a typical reservoir bank of a hydropower station in western China is taken as an example. The seepage characteristics and stability of the deposit body are calculated by using Geostudio series software. On this basis, the three-dimensional numerical simulation of the deformation of the deposit body is carried out by using FLAC-3D software. Through the comparison and analysis of the calculation results, the stability, deformation development trend and failure mode of the deposit body are summarized. It can provide reference for the comprehensive determination, monitoring arrangement and treatment of the similar deposit body.